ADVANCES IN AUGMENTED REALITY AND VIRTUAL REALITY IN MEDICAL EDUCATION: CHALLENGES AND FUTURE PERSPECTIVES - Vallim, Leonardo Henrique Suith; Prof. Me. João de Lucca Filho (Revista Interface Tecnológica, 2024)
In recent years, Augmented Reality (AR) and Virtual Reality (VR) have been progressively integrated into medical education, revolutionizing teaching and learning methodologies. These technologies provide immersive clinical simulations, allowing students to practice technical skills and make critical decisions in a safe and controlled environment. The article reviews the existing literature to discuss the main challenges in implementing AR and VR, including the disconnection between theory and practice, resistance to adoption, and the need for educator training. Additionally, the text addresses future perspectives for these technologies, emphasizing the importance of a curriculum that systematically integrates simulators and the advantages that AR and VR offer, such as more dynamic and effective learning experiences. By exploring the applications and benefits of these innovations, the article highlights the transformative potential of AR and VR in training more competent and well-prepared healthcare professionals.
Keywords: Augmented Reality; Virtual Reality; Medical Education; Educational Technologies; Medical Simulation